Readiness for Perception and Action: Towards a More Mechanistic Understanding of Phasic Alertness - Christian H. Poth (Journal of Cognition)
Human survival requires prompt perception and action to address relevant events in the environment. For this, the brain has evolved a system that uses warning stimuli to elicit phasic alertness, a state readying the brain for upcoming perception and action. Although a wealth of empirical evidence revealed how phasic alertness improves a wide range of perceptual and cognitive processing, it is still unclear by what cognitive mechanisms this is achieved. Here, we identify key problems that have to be solved for this to be possible and delineate concrete ways to achieve this. Specifically, we discover I) how to establish phasic alertness as a cognitive state of readiness for perception and action, II) how it can affect cognition online or offline, III) how it could be triggered internally without a warning, and IV) to what degrees it relied on bottom-up processing, or top-down temporal or stimulus expectations and the current task. As a result, the discussion provides us with a research program yielding the theoretical and empirical basis for mechanistic and computational models of phasic alertness and its neurophysiological underpinnings.